The moderating effect of coping behavior on academic stress and subjective well-being in students during the Covid-19 pandemic - Quarta, Dicky Listin; Nugraha, Sumedi P (Jurnal Psikologi Integratif, 2022)
This study aimed to observe the correlation between academic stress and subjective well-being, with coping behavior as a moderator in students during the COVID-19 pandemic. This involved 212 students in the UII. This study used the Perceived Stress Scale (18 items, a = 0.757), stress coping scale (44 items, a = 0.880), and college student subjective well-being questionnaire (16 items, a = 0.893). This study showed a significant negative correlation between academic stress and subjective well-being (β = -0.562; p < 0.05). Furthermore, the moderator regression analysis (MRA) results showed that the R² value of the interaction between academic stress and coping behavior as the moderator in the third regression model was higher than that of the other models (0.213). However, the increase was not statistically significant. The results showed that coping behavior did not have a moderating effect on the relationship between academic stress and subjective well-being.  Penelitian ini bertujuan untuk mengeksplorasi peran perilaku coping sebagai noderator hubungan antara stres akademik dan kesejahteraan subjektif pada mahasiswa selama pandemi COVID-19. Sebanyak 212 orang mahasiswa Universitas Islam Indonesia telah terlibat dalam penelitian ini. Perceived stress scale (18 item, a = 0.757), skala coping stress (44 aitem, a = 0.880), dan college student subjective well-being questionnaire (16 item, a = 0.893) merupakan alat ukur dalam penelitian ini. Penelitian ini menemukan hubungan antara stres akademik dan kesejahteraan subjektif yang negatif dan signifikan (β = -0.562; p < 0.05). Selanjutnya, hasil moderator regression analysis (MRA) menunjukan bahwa nilai R² pada model regresi ke-3 (i.e., model interaksi antara stress akademik dan perilaku koping) meningkat sebesar 0,213 meskipun peningkatan ini tidak signifikan. Peneliti menyimpulkan bahwa perilaku coping tidak mampu menjadi moderator dalam hubungan antara stres akademik dan kesejahteraan subjektif